Statics and mechanics of materials - Hibbeler, R. C. (Pearson Education Limited, 2019)
This book represents a combined abridged version of two of the author's book, namely Engineering Mechanics: Statics, Fourteenth Edition and Mechanics of Materials, Tenth Edition. It provides a clear and thorough presentation of both the theory and application of the important fundamental topics of these subjects, that are often used in many engineering disciplines. The development emphasises the importance of satisfying equilibrium, compatibility of deformation, and material behavior requirements. The hallmark of the book, however, remains the same as the author's unabridged versions, and that is, strong emphasis is placed on drawing a free-body diagram, and the importance of selecting an appropriate coordinate system and an associated sign convention whenever the equations of mechanics are applied. Throughout the book, many analysis and design applications are presented, which involve mechanical elements and structural members often encountered in engineering practice.